Types unite - Chow, Yean Li (Nanyang Technological University, 2023)
Languages are a means of communication with their own writing systems and character structures. However, when these visual differences are made more obvious with the inconsistent typographic choices between the English and Chinese language in bilingual posters, it obstructs how information is understood and navigated when these languages are placed together.